PENENTUAN JUMLAH TENAGA KERJA DI STASIUN PENGEMASAN BERDASARKAN STUDI WAKTU STANDAR DI CV. BINA AGRO MANDIRI - , NURUL WINDIANI PUTRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bina Agro Mandiri is a medium-scale industry fostered by CV Yogya Visiprima which engages in the processing of agricultural material products with its main raw material is simplisia that is made into herbal medicines in the form of herbs powder in capsules. The low awareness of the workers to work optimally affects a company in achieving the productivity height. It is due to an imbalance between the workload and the number of workers. This research was conducted which aimed to measure the workers standard time in respective packaging station operation, and to determine the number of the workers in the packaging stations based on the standard time. Thus, the number of the workers required according to the workload can be determined. Therefore, the workers can work effectively and efficiently. Based on the results of the workers number calculation performed in CV. Bina Agro Mandiri, apparently there is an imbalance of the workers in the packaging stations of the herbal medicine product. The number of the workers required is 17